THE DIFFICULTY LEVEL OF WRITING THE PROCEDURE TEXT FOR GRADE VIII STUDENTS IN JUNIOR HIGH SCHOOL 21 BENGKULU CITY - regitatririski_12; Epi Wadison; Ivan Achmad Nurcholis; Yupika Maryansyah (Teaching English and Language Learning English Journal, 2025)
This study aims to know the difficulties level in writing procedure text by Grade VIII Students at Junior High School 21 in Bengkulu City. This research design used descriptive quantitative method of research. The data collecting technique method used in this study was treatment. In this context, treatment research is referred to an intervention or treatment given to a research subject to observe a specific effect or outcome.  In analyzing the data in this study the researcher using a scoring formula, categorized the difficulty level and determines the level of difficulty. The findings from both assessments reveal that Grade 8th Students at Junior High School 21 Bengkulu City face significant challenges in writing procedure texts, with most aspects falling into the difficult category. In conclusion, the findings from both assessments indicates that the difficulty faced by Grade 8 students at Junior High School 21 Bengkulu City is at the difficult level in writing procedure texts, this difficulty caused by the generic structure and language features. This research can be used as a reference to conduct research related to procedural texts. Keywords: Difficulty, Writing, Procedure Text